Corporate Governance, Financial Transparency, Risk Management, and Corporate Reputation: How They Influence Gen Z Investor Confidence - Junaedi, Deddy; Rasna, Rasna; Sasmitha, Emdj Riesky (International Journal of Business, Law, and Education, 2025)
This study investigates the influence of corporate governance, financial transparency, risk management, and corporate reputation on Gen Z investor confidence. Using a sample of 300 Gen Z investors, the research employs multiple regression analysis to assess the relationships between these variables. The findings reveal that all four factors significantly and positively impact investor confidence, with corporate reputation and financial transparency having the strongest influence. The results highlight that Gen Z investors value companies that demonstrate ethical governance, transparent financial practices, strong risk management, and positive reputations. The study offers valuable insights for organizations aiming to attract and retain Gen Z investors, emphasizing the importance of maintaining high standards in governance, transparency, risk management, and corporate image.